Role of exposed crystal facets in the atmospheric pressure CO hydrogenation on Co3O4 - Jain, Preeti; Gupta, Sharad; Vinod, C. P. (Nano-Structures & Nano-Objects, 2020)
Co3O4 nanostructures with different exposed planes are studied for atmospheric pressure CO hydrogenation. Existence of different facets is characterized by HR-TEM and found Co3O4 - NSP (nanospheres) expose (112) facet, NB (nanobelts) exhibit (110) plane and (100) is the dominant surface facet in NC (nanocubes). Different catalytic activity is demonstrated by the specific facet of Co3O4 catalysts. CO hydrogenation is facet dependent and the catalytic activity follows the order of Co3O4-NB > Co3O4-NC > Co3O4-NSP.

Role of metal-support interaction for atmospheric pressure CO2 hydrogenation over Pd/(Ti)-SBA-15 catalyst: effect of titanium composition on products selectivity - Soni, Yogita; Gupta, Sharad; Vinod, C. P. (Molecular Catalysis, 2021)
The potential role of metal-support interaction for tuning the product selectivity during atmospheric pressure CO2 hydrogenation has been demonstrated on Pd/(Ti)-SBA-15 catalyst. Highly dispersed Pd NPs on SBA-15 (Pd/ SBA-15) was synthesized and further modified with titanium of varying composition. Comparison of catalytic activity of Pd/Ti-SBA-15 with its counterparts (Pd/SBA-15 and Pd/TiO2) illustrated the significance of strong PdTi interface in this catalyst and its role in tuning the product selectivity of CO2 hydrogenation. The generation of an ample amount of oxygen vacancies in the Pd/Ti-SBA-15 catalyst with maximum metallic Pd sites in close vicinity of Ti is proposed to boost the CO2 hydrogenation activity.
Keywords: CO2 hydrogenation; Metal-support interaction; Modified deposition precipitation; oxygen vacancies; Titanosilicates